Analysis of the Psychometric Properties of Perceived Motivational Climate in Sport Questionnaire and Its Relationship to Physical Activity and Gender Using Structural Equation Modelling - Cofre-Bolados, C (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
(1) Background: Different authors have established that each type of motivation to sports can favor healthy habits in men and women, being important to promote more self-determined motivations. (2) Methods: The present study was designed to assess selected psychometric properties of the Perceived Motivational Climate in Sport Questionnaire and study the relationship between motivational climate, physical activity and gender in adolescents. Research was conducted with a sample of 2134 Spanish children (12.5 ± 1.4 years). (3) Results: The final scale was formed of two factors. The fit of factor 1 (ego climate) was 0.867, the fit for factor 2 was 0.851 (task climate) and the overall fit was 0.765. Structural equation modelling identified a negative relationship between ego climate and task climate. This relationship was strong in women. A direct relationship was found between the ego climate and task climate in relation to physical activity in men and women. Nevertheless, this positive relationship was stronger in men. (4) Conclusions: PMCSQ-2 test is a good instrument to measure the motivation towards sports practice. Moreover, it is important to promote adaptive types of motivation in physical education classes in order to generate pleasure for learning and long-term physical activity engagement. © 2018 by the authors.